Malaysian Input-Output Research Association (Miora) School Of Economics, Faculty Of Economics And Business The National University Of Malaysia, UKM Bangi Selangor / Nurul Shakinah Mohamad Anwar - Mohamad Anwar, Nurul Shakinah (Universiti Teknologi MARA Cawangan Kelantan, 2014)
This research aims to evaluate the pull and push factors of motivation, tourist satisfaction and destination loyalty in Tioman Island. This study involved 215 of respondents by using stratified random sampling. Structural Equation Modeling (SEM) approach is used to investigate the relevant relationships among the variables. SEM also is a confirmatory method providing a comprehensive means for assessing and modifying the measurement models as well as structural model. The result of independent samples t-test and Analysis of Variance (ANOVA) shows a significant difference of the nationality, age, education level and monthly income towards tourist loyalty. In addition, the measurement model of motivation, satisfaction and loyalty of tourists shows a significant goodness of fit with value of Comparative Fit-Index (CFI) is 0.924 greater or equal 0.9 as a baseline comparison. In order to increase the number of tourists to come to Tioman Island, Ministry Tourism and Culture Malaysia should plays their role in order to increase the number of tourist arrival to this island